Pit and Fissure Sealants with Different Materials: Resin Based x Glass Ionomer Cement - Results after Six Months - Priscilla Santana Pinto Gonçalves; Tatiana Yuriko Kobayashi; Thais Marchini de Oliveira; Heitor Marques Honório; Daniela Rios; Salete Moura Bonifácio da Silva (Association of Support to Oral Health Research (APESB), 2016)
Objective: To compare the retention and superficial characteristics between a new resin-modified glass ionomer sealant and resin sealant. In addition, the teeth sealed were compared to partially erupted first molars (control group) without sealing in relation to the incidence of dental caries. Material and Methods: Initially, 31 children aged 6-8 years participated in this study. The study children showed caries history, but had at least two healthy first molars. A total of 114 teeth were randomly divided into three groups: Clinpro (n=36), Fluroshield (n=38), and control (n=40). The two sealants were applied under relative isolation after previous prophylaxis and enamel etching with phosphoric acid 35% (15s). Clinical evaluation was performed by two calibrated examiners. They evaluated the retention and surface characteristics of the occlusal surface. Results: Fluroshield® showed significantly greater retention than ClinproTM Varnish® XT (p=0.002). However, the performance analysis of the success and failure of retention presented no significant difference between the materials (p=0.141). Concerning to the surface characteristics, Fluroshield performed better than Clinpro after analyzing the marginal deterioration, marginal discoloration, and superficial discoloration (p<0.05). The surface texture of the materials under study was similar (p=0.071). Sealed groups (Clinpro=Fluroshield) showed similar performance in the prevention of dental caries, which was significantly lower than that of control group (p=0.001). Conclusion: Both sealants, Fluroshield® and Clinpro TM Varnish® XT were effective in preventing caries lesion within 6 months, although Fluroshield sealant showed better clinical retention.